2021
DOI: 10.1038/s41571-021-00476-2
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of CAR T cells in cancer therapy

Abstract: Chimeric antigen receptors (CAR) are fusion proteins that redirect T cell specificity towards surface molecules expressed on tumour cells independently of the conventional T cell receptor (TCR)-major histocompatibility complex (MHC) interactions. CARs are introduced into T cells through gene transfer 1,2 . The antigen-recognition domain most often consists of a mouse-derived monoclonal antibody as a continuous peptide single-chain variable fragment (scFv) steered through an extracellular spacer domain that pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
148
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 184 publications
(148 citation statements)
references
References 155 publications
(232 reference statements)
0
148
0
Order By: Relevance
“…Despite these advantages, allogeneic CAR T cells face formidable challenges. Foremost among these is controlling the risk of allo-rejection of infused cells by the recipient immune system and, to a lesser extent, the development of graft-versus-host disease (87). To overcome these issues, gene-editing methods such as CRISPR-Cas9, transcription activator-like effector nucleases (TALEN), or zinc finger nucleases (ZFN) have been used to disrupt the expression of endogenous T-cell receptors and/or MHC on the allogeneic T cells (refs.…”
Section: Moving From Autologous To Allogeneic Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite these advantages, allogeneic CAR T cells face formidable challenges. Foremost among these is controlling the risk of allo-rejection of infused cells by the recipient immune system and, to a lesser extent, the development of graft-versus-host disease (87). To overcome these issues, gene-editing methods such as CRISPR-Cas9, transcription activator-like effector nucleases (TALEN), or zinc finger nucleases (ZFN) have been used to disrupt the expression of endogenous T-cell receptors and/or MHC on the allogeneic T cells (refs.…”
Section: Moving From Autologous To Allogeneic Productsmentioning
confidence: 99%
“…3). While these promising approaches mitigate immunogenic recognition of MHC-deficient CAR T cells by host CD8 T cells, the infused cells become more prone to natural killer-cell killing (87). In addition, the tolerable number of potentially alloreactive CAR T cells infused into the recipient has yet to be established (87).…”
Section: Moving From Autologous To Allogeneic Productsmentioning
confidence: 99%
“…235 CAR T cell therapy has even induced anaphylaxis, an event thought to reflect the induction of an IgE response against murine scFv epitopes. 236 Methods to reduce CAR immunogenicity have been extensively reviewed by Wagner et al 237 and encompasses the removal of immunogenic CAR components, exchange of mouse-derived scFvs with humanised/ human scFvs, 238 eliminating immunogenic linkers through the use of heavy chain only CARs including nanobodies 239 and replacement of scFvs with receptorligand binding moieties. [240][241][242]…”
Section: Enhancing Car T Cell Efficacy By Refining Immunogenicity Of Target Bindersmentioning
confidence: 99%
“…Moreover, use of these technologies is likely to complement and enhance patient responsiveness and/or serve as an alternative to monoclonal antibody treatment that targets immune checkpoint inhibitors (ICIs), such as PD-1 or CTLA-4, which have been effective in only a subset of cancers. [117][118][119] Aside from the suitable safety documented in the above CRISPR-Cas9-based anti-tumor immunotherapy clinical trials, the small sample sizes and high variability in survival of individual patients limit definitive conclusions on the efficacy of these treatments. However, with a number of current CRISPR-based trials targeted toward boosting the immune response via manipulation of immune-related genes (Table 2), more conclusive results are likely to be seen during the coming months.…”
Section: Pd-1 Knockout T Cellsmentioning
confidence: 99%
“…Principally, in the context of cancer immunotherapy where potent immune activation is the goal, the extent of anti-Cas antibodies and/or T cells that may interfere with CRISPR-based treatment needs to be elucidated. 119,162 Recently, three studies have shown that both antibodies and T cells against Streptococcus pyogenes Cas9 (SpCas9) and Staphylococcus aureus Cas9 (SaCas9) are indeed present in many individuals, supporting that further investigation is required. First, Simhadri et al 163 highlighted that approximately 2.5% and 10% of donors (a predominantly white cohort from the United States) tested positive for anti-SpCas9 and anti-SaCas9 antibodies in human sera, respectively, by enzyme-linked immunosorbent assay (ELISA).…”
Section: Pre-existing Crispr Immunitymentioning
confidence: 99%